A dinâmica da (re) produção dos parques urbanos: um estudo do Parque Municipal Germano Augusto Sampaio em Boa Vista-RR - Bento, Márcio Baraúna (Universidade Federal de Roraima, 2019)
The present dissertation consists of an analysis of the spatialisation of the Urban Parks in Boa Vista-RR, and as a study the Germano Augusto Sampaio Municipal Park - PMGAS, located in the western zone of the city. The urban environment needs to be seen in multiple aspects, be they physical, social, economic or cultural and, in this perspective, Geography as a social science also has as object, society and space, that are worked in this research from the formation of Social Space. Thus, the research aims to understand the (re) production of the spaces from the territorialities in the Municipal Park Germano Augusto Sampaio - PMGAS. It is with this view that the research presents a geohistorical discussion to think of the urban parks, in experiences, urbanities and contemporaries, as well as the concept, typologies and role in the cities. It presents as a theoretical framework, Henri Lefébvre, in Marxist analysis, points out that space, understood as a social space, vivid, in close correlation with social practice. To reach the objective, the research adopts a methodological approach with qualitative technique, research and bibliographical reading, use of varied field research techniques such as behavioral maps, informal interviews with users and techniques of direct observation. Thus, the centrality of this research is based on the social practices exercised in the PMGAS and has shown in recent years, significant changes in human occupation in the places, and these are in permanent process of transformation. The analysis of the socio-spatial (re) production resulted in the identification of the territorialities in the PMGAS, as well as the reading of the object from the categories of analysis as form, function, structure and process. It is believed that, in addition to understanding the results, the problems and demands identified can provide information to future requalification projects and contribute to the planning of new public policies for the PMGAS.